2016
DOI: 10.1142/s0217751x16300593
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the holographic principle via RG flow

Abstract: This is a review of some recent works which demonstrate how the classical equations of gravity in AdS themselves hold the key to understanding their holographic origin in the form of a strongly coupled large N QFT whose algebra of local operators can be generated by a few (single-trace) elements. I discuss how this can be realised by reformulating Einstein's equations in AdS in the form of a non-perturbative RG flow that further leads to a new approach towards constructing strongly interacting QFTs. In particu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…The proposal in [1] is that the new action would be the holographic dual to that CFT giving a concrete realisation of the AdS/CFT correspondence. 1 1 Other similar proposals include [25][26][27][28][29][30][31][32][33][34], however, this paper will restrict its attention to testing QRG.…”
Section: Iteratementioning
confidence: 99%
“…The proposal in [1] is that the new action would be the holographic dual to that CFT giving a concrete realisation of the AdS/CFT correspondence. 1 1 Other similar proposals include [25][26][27][28][29][30][31][32][33][34], however, this paper will restrict its attention to testing QRG.…”
Section: Iteratementioning
confidence: 99%
“…Our biholographic construction however should not be thought of as a flow from an UV to an IR fixed point driven by a relevant deformation. 15 Rather the UV region in our case represents a strongly coupled version of usual perturbative dynamics, and the IR region represents the nonperturbative sector that exists as a shadow of the perturbative degrees of freedom in many-body quantum systems. In our case, the shadow IR theory and the hard-soft coupling constants will be determined by the parameters of the UV gravitational theory via:…”
Section: A Biholographic Illustrationmentioning
confidence: 99%
“…A natural question to ask is how we can achieve a RG flow description of the biholographic theory. The right framework is indeed a highly efficient RG flow as introduced in [13,14] (for a recent short review see [15]) which has been shown to reproduce the traditional holographic correspondence. In particular, this framework will allow us to define a conserved energy-momentum tensor of the full system at each scale without the need for introducing an action formalism.…”
Section: The Highly Efficient Rg Flow Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Strongly interacting theories on one side of the duality are mapped to weakly interacting theories on the other side, granting a method to perform non-perturbative computations. [39,40] Modern approaches to the holographic principle tend to view the additional dimension in the bulk quantum gravity theory as corresponding to renormalisation length scale in the boundary theory [41]. For conformal field theories this means the scale invariance of the theory would force the bulk theory to be the same regardless of how far into the bulk you moved.…”
Section: The Holographic Principlementioning
confidence: 99%